Fenomena Tenaga Kerja Ilegal Asal Dusun Cangkringan, Sumberjo, Kandat, Kediri - Jati Pamungkas; Diyah Mahbubatul Rahmawati (Realita: Jurnal Penelitian dan Kebudayaan Islam, 2021)
This study aims to determine the experience of workers with ilegal status from villages who work in Malaysia. The author wants to know the experience of ilegal workers and wants to know the factors that cause them to become workers with ilegal status. The research method used in this study is a phenomenological method with a qualitative approach. While the theory used in this research is phenomenological theory. The results of the study indicate that there are problems that cause Indonesian workers (TKI) to decide to work in the destination country, namely economic factors and they think that working as TKI is a solution to the economic problems that suffocate them. Meanwhile, their ilegal status is suspected to be due to limited capital to apply for permits to work.